PENANAMAN KARAKTER CINTA TANAH AIR MELALUI LAGU NASIONAL DI KELAS B TK KEMALA BHAYANGKARI 55 SURAKARTA - Fikri Nailatsani, Hana; Paulus Widjanarko; Yetty Isna Wahyuseptiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of instilling the character of patriotism from an early age amidst the challenges of globalization, which may reduce children's sense of nationalism. One effort that can be made is through the use of national songs as learning media that are suitable for the characteristics of early childhood. This study aims to describe the process of instilling the character of patriotism through national songs and the media used in learning activities in Class B of TK Kemala Bhayangkari 55 Surakarta. This study employed a descriptive qualitative approach with a case study strategy. The research subjects consisted of classroom teachers and the principal. Data collection techniques were carried out through interviews, observations, and documentation, while data validity was ensured through technique and source triangulation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the cultivation of patriotic character was carried out through habituation activities by routinely singing national songs during the opening activities of learning sessions. The learning process was implemented through imitation methods, repetition, and explanation of song meanings using simple language related to children’s daily lives. The media used included digital television, speakers, song videos, and supporting pictures, which proved effective in increasing children’s interest and understanding. However, the activities still tended to focus on memorization aspects, so the interpretation and understanding of the songs need to be strengthened further. Evaluation was conducted through behavioral observation and simple question-and-answer activities to assess children’s understanding and attitudes. Thus, national songs can serve as an effective medium for instilling the character of patriotism in early childhood when accompanied by habituation, appropriate meaning-making, and the use of engaging and interactive learning media.Keywords: character planting, early childhood, religious and moral values, habituation, kindergarten